2017
DOI: 10.1016/j.archoralbio.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of salivary oral bacteria according to the severity of dental caries in childhood

Abstract: This study aimed to assess differences in selected oral bacteria in children according to the severity of dental caries. One hundred and thirty-six children, 36-60 months old were divided into three groups according to caries status: caries-free (CF) (n=47), early childhood caries (ECC) (n=40) and severe-early childhood caries (S-ECC) (n=49). Saliva was collected for detection and quantification of selected oral streptococci, Actinomyces naeslundii, Lactobacillus spp., Bifidobacterium spp., and Scardovia wiggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
1
21
2
1
Order By: Relevance
“…A previous study found that mutans streptococci, which have high cariogenic potential, can reduce the environmental pH to 3.5 (Aizawa et al, 2009), which suggests that the acid productivity and acid tolerance of S. wiggsiae are equivalent to those of S. mutans. This might be one of the reasons why S. wiggsiae is frequently detected in caries lesions (Tanner et al, 2012;Colombo et al, 2017;Chandna et al, 2018). As was reported for Bifidobacterium dentium and Bifidobacterium longum, acetic acid was the main acidic end-product by S. wiggsiae (Table 1), whereas many cariesassociated bacteria, such as mutans streptococci, predominantly produce lactic acid (Manome et al, 2019).…”
Section: Discussionmentioning
confidence: 68%
“…A previous study found that mutans streptococci, which have high cariogenic potential, can reduce the environmental pH to 3.5 (Aizawa et al, 2009), which suggests that the acid productivity and acid tolerance of S. wiggsiae are equivalent to those of S. mutans. This might be one of the reasons why S. wiggsiae is frequently detected in caries lesions (Tanner et al, 2012;Colombo et al, 2017;Chandna et al, 2018). As was reported for Bifidobacterium dentium and Bifidobacterium longum, acetic acid was the main acidic end-product by S. wiggsiae (Table 1), whereas many cariesassociated bacteria, such as mutans streptococci, predominantly produce lactic acid (Manome et al, 2019).…”
Section: Discussionmentioning
confidence: 68%
“…HOT 448 [34] observed in dentin caries in the current report. S. wiggsiae is a relatively newly recognized species that has been detected in caries in several reports from the US [5], Europe [35] and Brazil [36]. Other highly acidogenic, lactate-producing species in dentin included A. rimae and A. parvulum [37] although the acid tolerance of these species is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Two pairs of primers (for S. mutans and L. fermentum) were used based on the published primer protocols ( Table 1). Another two pairs of new primers (for P. pallens and P. denticola) were designed using AlleleID 6.0 (Premier Biosoft, Palo Alto, CA, USA) for qPCR and then analyzed in BLASTn (https://blast.ncbi.nlm.nih.gov/Blast.cgi?PAGcE_TYPE=BlastSearch) 1 . Species specificity for the primers of P. denticola and P. pallens were tested by conventional (Fig.…”
Section: Design Of Quantitative Qpcr Primersmentioning
confidence: 99%